2012
DOI: 10.1075/li.35.2.11sta
|View full text |Cite
|
Sign up to set email alerts
|

Negation marking in French text messages

Abstract: This study investigates the drop of the first clitic element, ne, of French sentential negation. It is based on 4,628 French text messages taken from the newly established corpus sms4science.ch. It shows that regional or stylistic factors do not play a major role in triggering ne deletion or ne retention, and that the only relevant language-internal factor is subject type, more precisely clitic subjects (also in subject doubling structures) and subject drop, which seem to favour or even trigger categorically n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…The results of the logistic regression confirmed that both linguistic and sociostylistic factors continue to influence ne retention in contemporary French. These results differ from Stark (2012), who suggested that ne was no longer influenced by sociolinguistic factors and was conditioned only by linguistic factors. That the present NSs vary their use of ne to mark emphasis, to quote speech from a more formal register, and to signal serious topics suggests that ne still carries sociostylistic value.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of the logistic regression confirmed that both linguistic and sociostylistic factors continue to influence ne retention in contemporary French. These results differ from Stark (2012), who suggested that ne was no longer influenced by sociolinguistic factors and was conditioned only by linguistic factors. That the present NSs vary their use of ne to mark emphasis, to quote speech from a more formal register, and to signal serious topics suggests that ne still carries sociostylistic value.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar patterns emerge in studies of internet chat and text-messages (Stark, 2012;van Compernolle, 2008, whose sociolinguistic norms closely resemble those of casual speech despite the written medium (van Compernolle, 2008). The type of postverbal negator has also been reported to influence ne retention.…”
Section: Linguistic Factorssupporting
confidence: 53%
See 2 more Smart Citations
“…(2013), Thurlow/Poff (2013), Herring/Androutsopoulos 2015, and most recently, Dürscheid/Frick (2016) have analyzed multiple aspects of CMC, with a clear focus on graphematical, interactional and pragmatic aspects. 3 Swiss text messages, the very first popular form of mobile graphic communication, have been intensely investigated, as can be seen in the aforementioned books and also from the articles and monographs written in the context of the Swiss SNSF research project "SMS communication in Switzerland" (project number: CRSII1_136230): see, e. g., Bucher (2016), Cathomas (2015), Cathomas et al (2015), Jucker/Dürscheid (2012), Grünert (2011), Morel et al (2012), Morel (2016), Frick (in print), Stark (2012), Robert-Tissot (2015), Ueberwasser (2013). 4 In contrast to this, and quite surprisingly given the omnipresence of mobile messengers in our daily lives, systematic research on WhatsApp messages is, at the time of writing, quite lacking.…”
Section: Introductionmentioning
confidence: 99%